2021
DOI: 10.1007/s00592-020-01668-5
|View full text |Cite
|
Sign up to set email alerts
|

Fat mass and obesity-associated (FTO) gene epigenetic modifications in gestational diabetes: new insights and possible pathophysiological connections

Abstract: Aims Gestational diabetes mellitus (GDM) can lead to short- and long-term complications for the child. Epigenetic alterations could contribute to explaining the metabolic disturbances associated with foetal programming. Although the role of the FTO gene remains unclear, it affects metabolic phenotypes probably mediated by epigenetic mechanisms. The aim of this study was to assess whether placental DNA epigenetic modifications at FTO promoter-associated cysteine–phosphate–guanine (CpG) sites are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 80 publications
1
10
0
1
Order By: Relevance
“…Furthermore, for participants with the FTO risk allele (AA), the expression of miR-22-5p was downregulated. One known target of miR-22 is the histone deacetylase 4 ( HDAC4 ) [ 39 ], supporting the theory that metabolic phenotypes are probably mediated by epigenetic mechanisms due to the different FTO mutations [ 40 ]. These results highlight the importance of personalized analysis and interventions, as the epigenetic phenotype varies significantly depending on the genotype.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, for participants with the FTO risk allele (AA), the expression of miR-22-5p was downregulated. One known target of miR-22 is the histone deacetylase 4 ( HDAC4 ) [ 39 ], supporting the theory that metabolic phenotypes are probably mediated by epigenetic mechanisms due to the different FTO mutations [ 40 ]. These results highlight the importance of personalized analysis and interventions, as the epigenetic phenotype varies significantly depending on the genotype.…”
Section: Discussionmentioning
confidence: 92%
“… No data on foetal sex Sletner et al, 2021 [ 90 ] 33 GDM 27 Ctrl PS FTO No association between FTO DNAm and GDM. No data on foetal sex Franzago et al, 2021 [ 91 ] 23 GDM 23 Ctrl MethylTarget Technique MEG3 DNAm was increased in GDM, and positively associated with birthweight and fasting glucose levels. No data on foetal sex Chen et al, 2021 [ 92 ] 20 GDM 16 Ctrl 450k EWAS 662 CpGs with differential DNAm in GDM (without FDR).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro , FTO efficiently eliminated the m6A modification of mRNA ( 56 ). Recently, some studies have found strong associations between FTO and hypertension ( 57 ), diabetes ( 58 , 59 ), obesity ( 60 , 61 ), non-alcoholic fatty liver disease ( 62 , 63 ), atherosclerosis ( 64 ), myocardial infarction ( 38 , 65 ), ischemic reperfusion injury ( 65 ), cardiac hypertrophy ( 65 ), and heart failure ( 65 ). Thus, FTO considerably contributes to the progression of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%